Competency-Based Approach in Differentiated Instruction of English for Specific Purposes to it-Students - Synekop, Oksana (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article considers the competency-based approach in differentiated instruction of English for specific purposes at university level. It also outlines professional communicative foreign language competence and interdisciplinary competence for successful differentiated instruction of English for specific purposes to information technology students of universities.
Keywords: differentiated instruction; English for specific purposes; professional communicative foreign language competence; interdisciplinary competence; information technology students; university